2015
DOI: 10.7205/milmed-d-14-00382
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Adverse Effect of Nicotine and Physical Strain on Human Gingival Fibroblasts as a Model of the Healing of Wounds Commonly Found in the Military

Abstract: Initial treatment of HGF wounds with CMS resulted in faster wound repopulation regardless of nicotine presence. By day 6, wound healing of HGF exposed to both nicotine and CMS is delayed. These findings suggest that CMS and nicotine may affect fibroblasts and delay wound healing at other sites in the body as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
3
0
4
Order By: Relevance
“…VEGF plays an important role as a regulator in physiological vascular development, being a widely studied angiogenic factor; in tissues where angiogenesis is increased, its expression is considerably high . Evaluation of the presence of VEGF in the skin grafts points to higher values of VEGF related to greater viability of the skin graft, probably because of the influence on local angiogenesis . In the present study, the groups that were stimulated with PBM showed a higher amount of VEGF when compared with the other groups, demonstrating that the PBM can increase the amount of newly formed vessels in the tissue.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…VEGF plays an important role as a regulator in physiological vascular development, being a widely studied angiogenic factor; in tissues where angiogenesis is increased, its expression is considerably high . Evaluation of the presence of VEGF in the skin grafts points to higher values of VEGF related to greater viability of the skin graft, probably because of the influence on local angiogenesis . In the present study, the groups that were stimulated with PBM showed a higher amount of VEGF when compared with the other groups, demonstrating that the PBM can increase the amount of newly formed vessels in the tissue.…”
Section: Discussionsupporting
confidence: 50%
“…Smoking is detrimental to healing in both the acute and chronic phases, negatively influencing the fibroblastic activity, epithelialization, and immune response. Necrosis is three times higher in smokers, inhibiting the flow of oxygen to healing tissues (vasoconstriction), and elevated carboxyhemoglobin levels in the blood result in decreased oxygen tension in tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Effects on HGFs of 1 mg/mL (i.e., 6.1 mM) nicotine, very close to the widely used 5 mM, 17 , 18 which has been demonstrated to be the concentration present in the saliva of smokers 19 was further investigated. Having demonstrated 12 , 20 that the high levels of ROS production and the occurrence of apoptosis are associated with exposure to e‐cigarette fluids, electron microscopy analyses were performed to determine the effects of these fluids on other features of cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A nicotina liberada do fumo acarreta um efeito vasoativo limitado na pele e tecido subcutâneo, o que claramente reduz o fluxo sanguíneo do tecido, comprometendo o metabolismo aeróbio, e é reconhecida como principal causadora de complicações pósoperatórias de feridas em indivíduos fumantes (Sørensen et al, 2009;Xanthoulea et al, 2013;Dinos et al, 2015;Pluvy et al, 2015), interferindo na síntese de colágeno, e prejudicando o processo de cicatrização (Jorgensen et al, 1998;Biondo-Simões et al, 2009).…”
Section: Introductionunclassified